Relevansi Tasawuf dalam Mengatasi Stress dan Kecemasan pada Remaja Di Era Modern - Arrasyid, Arrasyid; Deswita, Pipi; Syakira Hsb, Nurul Intan; Putri, Santi Syah; Hidayati, Diken Sukma (JURNAL AL-AQIDAH, 2024)
This article investigates the applicability of Sufism is as a therapeutic strategy for adolescents experiencing stress and anxiety in the contemporary world. This article explores how Sufism's tenets—meditation, reflection, and religious values can benefit teens' mental health in light of the psychological difficulties that today's generation is facing. This article offers an understanding of the application of pertinent Sufism methods to young people everyday situations as a useful tool for anxiety and depression management through an analysis of the available literature and empirical analysis. It is hoped that this knowledge will significantly aid in the creation of comprehensive approaches and techniques for intervention for teenagers mental health in the stressful modern world.